2017
DOI: 10.1089/ten.tec.2016.0264
|View full text |Cite
|
Sign up to set email alerts
|

Human, Tissue-Engineered, Skeletal Muscle Myobundles to Measure Oxygen Uptake and Assess Mitochondrial Toxicity

Abstract: Mitochondrial dysfunction is responsible for the toxicity of a number of drugs. Current isolated mitochondria or cellular monoculture mitochondrial respiration measurement systems lack physiological relevance. Using a tissue engineering rather than cell- or mitochondria-based approach enables a more physiologically relevant detection of drug-induced mitochondrial impairment. To probe oxygen consumption and mitochondrial health, we assayed the bioenergetic profile of engineered three-dimensional human skeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Over the past two decades, approaches for engineering 3D muscle bundles have been advanced and refined. Several different types of culture chambers with anchor points have been fabricated ( Costantini et al, 2017a ; Smith et al, 2016 ), including Velcro and nylon frames ( Davis et al, 2017 , 2019 ; Madden et al, 2015 ; Rao et al, 2018 ; Smith et al, 2016 ; Zhang et al, 2018 ) and microfabricated chambers with pillars ( Osaki et al, 2018 , 2020 ; Uzel et al, 2016 ). Testing of multiple ECM solutions has also revealed that fibrin hydrogels are optimal for encapsulating myotubes due to their strength ( Hinds et al, 2011 ; Pollot et al, 2018 ), although these hydrogel compositions are not necessarily physiological.…”
Section: Engineered In Vitro Models Of Neuromusculmentioning
confidence: 99%
“…Over the past two decades, approaches for engineering 3D muscle bundles have been advanced and refined. Several different types of culture chambers with anchor points have been fabricated ( Costantini et al, 2017a ; Smith et al, 2016 ), including Velcro and nylon frames ( Davis et al, 2017 , 2019 ; Madden et al, 2015 ; Rao et al, 2018 ; Smith et al, 2016 ; Zhang et al, 2018 ) and microfabricated chambers with pillars ( Osaki et al, 2018 , 2020 ; Uzel et al, 2016 ). Testing of multiple ECM solutions has also revealed that fibrin hydrogels are optimal for encapsulating myotubes due to their strength ( Hinds et al, 2011 ; Pollot et al, 2018 ), although these hydrogel compositions are not necessarily physiological.…”
Section: Engineered In Vitro Models Of Neuromusculmentioning
confidence: 99%
“…[9,255] Unforeseen mitochondrial toxicity is the most common cause for failure of candidate drugs identified from in vitro drug screens in preclinical animal models. [256] This can be attributed to the Crabtree effect, [257] where in vitro cultured cells typically utilize glycolysis to generate ATP despite the presence of abundant oxygen and functional mitochondria.…”
Section: Disease Modeling With Engineered Human Musclementioning
confidence: 99%
“…Muscle biopsies were obtained from discarded surgical waste with Duke IRB approved protocols. Human skeletal muscle myoblasts were isolated according to previously described methods 12 . Briefly, muscle samples were minced, washed in phosphate buffered saline (PBS), and enzymatically digested in 0.05% trypsin for 30 minutes.…”
Section: Primary Human Myoblast Culturementioning
confidence: 99%
“…The myobundle assembly procedure was used as previously described 9,12,29 . Briefly, cells were dissociated in 0.025% trypsin-EDTA to a single cell solution then encapsulated in a fibrinogen (Akron, Boca Raton, FL) and matrigel solution on laser cut Cerex frames within PDMS molds at 7.5 × 10 5 cells/myobundle.…”
Section: Human Tissue-engineered Skeletal Muscle Bundle Culturementioning
confidence: 99%